PERSFEKTIF HUKUM ISLAM TERHADAP TANGGUNG JAWAB (HADHANAH) KEPADA ANAK KETIKA ORANG TUA BERCERAI - Faiz Zainuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2023)
There are many things that should be asked by husband and wife when deciding to divorce. In addition the property of gono-gini, another thing that must be considered is the division of child custody in a divorce. by both parents may not injure the fulfillment of children's rights which are also regulated by the state through the child custody law through Law Number 23 of 2002 concerning Child Protection. In General Provisions Article 1 point 11 it is explained that foster care is the power of parents to nurture, educate, nurture, nurture, protect, and develop children according to their religion and abilities, talents and interests. According to Article 41 of Law Number 1 of 1974 concerning Marriage, a married husband and wife are still obliged to maintain and educate their children for the benefit of the child himself. Divorce also does not cancel the father's obligation to be responsible for all the care and education that the child needs. However, the court may decide that the mother also demands it under certain conditions. The court also has the right to determine which custody of the child should be given to the mother or father, especially if there is a right to household rights.